Gycklare och socialrealistisk skildrare: Karnevalism, klass och genus hos Dolly Parton - Greiff, Mats (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
Dolly Parton is one of the universally most beloved, and most widely respected women emerged from country music. In the article her lyrics is analysed from a class and gender perspective. The partly radical content of the lyrics is related to her carnivalesque outlook. The contradiction between the lyrics and Parton's outlook is pointed out as the main reason to her widespread popularity.